(untitled) (Research, Society and Development, 2021)
This article consists of an outline of the Master’s research of the PPGEn Program, UNIC-IFMT, in a partial process, which addresses the cycle of human formation in the municipal education network of Cuiabá and the relationship with the Common National Curricular Base. The main objective was to understand the fragmentation process and the existing disruptions in the development of teaching-learning practices. In this sense, the study consisted of a participatory research, where an interview script was established, which was used as an instrument for data analysis. The interviews were with teachers from elementary school I. Three schools in Cuiabá were part of the research. The investigation went on to unveil the ruptures and fragments existing within the human formation cycle, in the theoretical and practical aspects, of the teacher’s previous knowledge, analyzing the curriculum in relation to the cultural and social reality of the student, within a time-space. Therefore, this research aimed to understand, as the teaching-learning process takes place, in the respective interviewed schools, respecting their right to learning, thus attending an integral education, supported by the BNCC. It is known that this individual is part of a plurality, which must be introduced in the teaching-learning process, making this knowledge meaningful and pleasurable. The partial results of the research show that the teacher’s pedagogical practice needs to be better understood in the time-space that the student is inserted in, this process needs a reflection in relation to the different levels in the classroom, respecting the time-space of the subject of the pedagogical action, in an integral construction.